Contour ridge modelling using fuzzy logic and process based approaches for improved rainwater harvesting - Mhizha, Alexander (My University, 2017)
Rainwater harvesting is used as a way of improving crop yields in rain fed agriculture by capturing excess rainfall and storing it in-situ or in reservoirs for use during dry spells. Contour ridges are one of the many rainwater harvesting technologies that are used although little is known about their effectiveness. Contour ridges harvest runoff generated in the cropped field upstream of the ridges. The traditional contour ridge type in Zimbabwe was introduced by the government in the 1950s to control soil erosion through safely draining away runoff from cropped fields and is commonly referred to as graded contour (GC) ridges. In the 1990s the country experienced severe and more frequent droughts leading stakeholders to experiment on contour ridges that retain the runoff instead of draining it away which are known as dead level contour (DLC) ridges. There was therefore the need to find out if there are benefits derived from this change and assess conditions under which benefits would be experienced. Previous studies have shown that rainwater harvested by contour ridges can improve water availability in downstream fields. However these studies did not investigate the conditions under which such benefits are realised. In addition no attempt to model water harvesting by contour ridges have been made in Zimbabwe while the contour ridges are widely being used for soil and water conservation. This research investigated the effect of contour ridges by comparing soil moisture between plots with DLC and GC ridges using plots with no contours as a control. Experimental work was carried out in Zhulube, in Matebeleland South Province of Zimbabwe. Matebeleland South Province falls within the semi-arid area in which rainfall is characterised by mid-season dry spells leading to frequent crop failure. In addition, the area often receives high rainfall intensities leading to soil erosion and sedimentation of rivers. DLC and GC ridges were constructed in farmers’ fields where maize crops were planted. Soil moisture measurements were done using a micro gopher soil moisture profiler while runoff plots were used to measure runoff generation. A fuzzy model was developed using data from this experiment and a previous study in Masvingo Province of Zimbabwe to simulate runoff generation at field scale while a process based water balance model was also developed to simulate soil moisture changes within the root zone of the cropped area. The results from this study indicate that DLC are effective in clay and loamy soils where runoff generation is significant and not in sandy soils due to insignificant generation of runoff under the rainfall regimes of semi-arid areas. Fuzzy logic was found to be a useful method of incorporating uncertainty in modelling runoff at field scale. A mass water balance model developed on process based principles was able to model soil moisture in the root zone reasonably well (NSE =0.55 to 0.66 and PBIAS=-1.3% to 6.1%) and could help to predict the water dynamics in contour ridged areas as would be required in determining the suitable dimensions and spacing of contour ridges. Further research is required to improve the fuzzy component of the model for estimation of runoff when more data becomes available. In addition experiments to validate methods of estimating macro pore fluxes and lateral transfer of water from the contour ridge channel to the downslope field are also recommended. The model structure can be improved by adopting the representative elementary watershed approaches to include momentum and energy balances in addition to mass balance that was used in this study.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Doctor of Philosophy. Johannesburg, February 2017
Keywords: Water harvesting; Rainwater; Fuzzy logic